Hambatan Sosial dalam Pembangunan Ekonomi terhadap Pertumbuhan UMKM di Kecamatan Kraksaan, Kabupaten Probolinggo - Ismatur Rohmaniyah; Intan Nur Faizah; Hikmatul Mufidah (CV. ITTC INDONESIA, 2026)
This study aims to analyze social barriers in economic development that affect the growth of Micro, Small, and Medium Enterprises (MSMEs) in Kraksaan District, Probolinggo Regency. MSMEs play a strategic role in supporting regional economic development; however, their growth is often constrained by various non-economic factors, particularly social barriers. This research employs a descriptive qualitative approach through a literature review, utilizing secondary data obtained from academic journals, reference books, and relevant institutional reports. Data analysis is conducted descriptively to identify the forms of social barriers faced by MSMEs and to examine their implications for business growth and competitiveness. The findings reveal that MSMEs encounter several dominant social challenges, including low levels of business literacy, traditional entrepreneurial mindsets, limited access to information and business networks, and low utilization of technology in business activities. These conditions hinder MSMEs from innovating, expanding market access, and improving productivity, which ultimately weakens their competitiveness. Therefore, strengthening social aspects such as education, mindset transformation, information accessibility, and technological adaptation is essential to support sustainable MSME growth and enhance regional economic development.